Effect of Organic Amendments on Soil Structure: A Review - Fattah, Mahdi Fahmi (American Journal of Botany and Bioengineering, 2025)
Organic additions are prominent in the enhancement of physical aspects of soil and the agricultural output of the land. Recent scientific research on the effects of organic material on the soil properties, specifically physical structure, aggregate forming, structural stability, porosity, elasticity and water holding capacity is synthesised in this review. The literature reveals that the addition of farmyard manure, plant and animal residues, compost, and biochar has a significant positive impact on soil structural stability and physical properties. The extent of the enhancement is governed by the nature of organic amendment, application rate as well as the inherent properties of soil. In general, the evidence implies that the rational and science-based application of organic amendments can help to make the soils productive in the short term and minimise the soil degradation in the long term.